Akhlak Based Digital Literacy: Islamic Education's Role in Mitigating Adolescent Cyberbullyin Among Muslim Adolescents - Farkhan Syahrul Mubarok; Slamet Untung; Thibtum Mujabah; Nok Uzana; Zanuba Qotrunnada (MADINAH, 2025)
The rapid development of information and communication technology has transformed social interaction patterns among adolescents, particularly through digital platforms such as social media and messaging applications. Along with these advancements, new challenges have emerged, including the rise of cyberbullying, which manifests in the form of insults, slander, threats, and other forms of online harassment. This phenomenon negatively affects adolescents’ mental health, self-esteem, and social well-being. For Muslim youth, cyberbullying is not only a social problem but also a moral issue that contradicts Islamic ethical principles. Islamic teachings emphasize kindness, responsibility, and respectful communication, both offline and online. This research employs a library research method to analyze the role of Islamic Religious Education (PAI) in addressing cyberbullying based on literature from credible academic sources. The findings reveal that PAI contributes significantly as a moral protector, a foundation for Islamic-based digital literacy, a medium for character development, and a guide for teachers to act as digital role models. Despite its effectiveness, challenges remain in curriculum relevance, digital integration, and teaching quality. Therefore, strengthening curriculum innovation, enhancing teacher competence, and fostering collaboration between schools, families, and communities are necessary to optimize the role of Islamic Religious Education in preventing cyberbullying.